Role of mineral elements in the nutrition of garden strawberry plants - L. А. Marchenko; S. V. Akimova; A. V. Solovyov; S. S. Makarov; E. G. Samoshenkov; G. E. Ter-Petrosyants; A. V. Zubkov (Овощи России, 2024)
Relevance. The increase in global production of garden strawberry fruit is due to the high demand for the products for fresh consumption and as raw material for processing. The leading countries are: PRC, USA, Turkey, Egypt, Mexico, Spain, Russia, Poland, South Korea, Brazil. Increase in production volumes is provided due to high productivity of new varieties and intensification of strawberry cultivation technologies and, in particular, plant nutrition. The possibility of managing the nutrition of garden strawberry plants is one of the priority tasks from the solution of which depends on the realization of the potential of plant productivity, as well as the quality of the resulting products The role of many macroand microelements in plant nutrition is not fully understood. Numerous studies are conducted to identify the mechanisms of their absorption and movement in strawberry plants. New forms of fertilizers are being studied, allowing to effectively influence the processes of growth and development of plants, minimize the impact on the environment.Results. The article is devoted to the review of the role of the main mineral macroand microelements in plant nutrition, such as nitrogen, phosphorus, potassium, magnesium, calcium, iron, silicon, molybdenum. Based on the analysis of literary sources, the influence of certain mineral elements on physiological processes associated with the growth and development of garden strawberries is considered. The data on reaction of plants to the optimal content, excess and deficiency of certain elements, possibilities of their receipt and assimilation by plants of garden strawberries are given. Application in practice of the world experience on management of mineral nutrition can significantly improve the existing technologies of strawberry cultivation in open and protected ground.